The Japanese registry for surgery of ischial pressure ulcers: STANDARDS-I. (1st September 2020) - Yanagi, Hideyuki; Terashi, Hiroto; Takahashi, Yoshimitsu; Okabe, Katsuyuki; Tanaka, Katsumi; Kimura, Chu; Ohura, Norihiko; Goto, Takahiro; Hashimoto, Ichiro; Noguchi, Madoka; Sasayama, Junichi; Shimada, Kenichi; et al.
Abstract : Objective: To clarify the surgical indications and the appropriate perioperative management of ischial pressure ulcers (PUs). Method: A two-year prospective, nationwide registry study was carried out across 26 medical institutions in Japan. All participating institutions managed ischial PUs according to the standardisation of total management and surgical application for the refractory decubitus (STANDARDS-I) perioperative protocol. Analysis was conducted on a range of clinically or statistically important variables for the achievement of primary or secondary endpoints: complete wound healing and hospital discharge at three months, and complete wound healing at one month after surgery, respectively. Results: A total of 59 patients took part in the study. All patients underwent surgery for ischial PUs during the study period. Patients who had achieved the primary endpoint had a higer preoperative functional independence measurement (FIM score), a higher 'G' score in the DESIGN-R scale and were more likely to have healed by primary intention. Patients who had achieved the secondary endpoint were more likely to have spastic paralysis, preoperative physiotherapy and localised infection of the wound, among other variables. Conclusion: This survey suggests that preoperative physiotherapy increases the speed of wound healing, and good granulation of the wound bed preoperatively increases the likelihood of woundless discharge from hospital, whereas the existence of comorbidities negatively influences the likelihood of woundless discharge from hospital. The study also suggests that the existence of spastic paralysis, preoperative infection of the wound, or surgical reduction of the ischial tubercle speeds up the healing of the wound. However, the wound failed to heal significantly more often in patients with increasing white blood cell count after surgery.